Online Eye-Tracking: Observing the Attention of Pre-service Chemistry Teacher from Non-Science Backgrounds in Solving Chemistry Problems - Khairiatul Muna; Helda Rahmawati; Muhammad Bahit; Saipul Rasid; Lutfiana Marisa; Rosana Rosana; Nurul Istiqamah (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Recent advances in online eye-tracking allow researchers to capture eye movements as visible markers of attentional processes. This study adopts a mixed-methods design using webcam-based eye tracking via the RealEye platform to profile the attentional patterns of pre-service chemistry teachers who completed non-science tracks in high school. Two participants from the Chemistry Education program at UIN Antasari Banjarmasin undertook a problem-solving task in chemistry; their eye movements were recorded and analyzed descriptively. In framing attention, we distinguish between overt orientation—shifts in gaze toward a target—and covert orientation—mental shifts of focus without corresponding eye movements. Findings indicate that both participants required a comparatively longer time to observe, read, and solve the given problems. These attentional profiles align with their problem-solving outcomes, which fell into the medium and low performance categories. The results suggest that a non-science secondary background may be associated with less efficient visual strategies when tackling chemistry tasks. Targeted instructional support—such as scaffolded practice with chemical representations and stepwise problem decomposition—may therefore be warranted in teacher-education curricula.